The era of the wandering mind? Twenty-first century research on self-generated mental activity - Callard, Felicity; Smallwood, Jonathan; Golchert, Johannes; Margulies, Daniel S. (Frontiers in Psychology, 2013)
The first decade of the twenty-first century was characterized by renewed scientific interest in self-generated mental activity (activity largely generated by the individual, rather than in response to experimenters’ instructions or specific external sensory inputs). To understand this renewal of interest, we interrogated the peer-reviewed literature from 2003–2012 (i) to explore recent changes in use of terms for self-generated mental activity; (ii) to investigate changes in the topics on which mind wandering research, specifically, focuses; and (iii) to visualize co-citation communities amongst researchers working on self-generated mental activity. Our analyses demonstrated that there has been a dramatic increase in the term “mind wandering”, and a significant crossing-over of psychological investigations of mind wandering, specifically, into cognitive neuroscience. If this is, indeed, the ‘era of the wandering mind’, our paper calls for more explicit reflection to be given by mind wandering researchers to the terms they use, the topics and brain regions they focused on, and the research literatures that they implicitly foreground or ignore as not relevant.